Electrostatic resonance-cone waves emitted by a dipole in the ionosphere. - James, H.C (IEEE Transactions on antennas and propagation)
The theory of whistler-mode radiation from a dipole antenna has been tested in the ionospheric sounding-rocket experiment OEDIPUS-C (OC). In this bistatic investigation, 25-kHz waves were received at a distance of 1200 m from a synchronized transmitter. Electric fields near the group resonance cone were significantly stronger than in other directions, as predicted by theory. The transmitting antenna RF current was obtained from an equivalent circuit including an antenna impedance predicted by quasistatic theory. This current was applied to resonance-cone radiation theory. Observed radiated levels are about a hundred times greater than theoretical predictions based on some assumptions about the electromagnetics of the transmitting and receiving antennas. The modulation of the received signal caused by the spins of the transmitting and receiving dipoles was consistent with the electric field being polarized predominantly along the electrostatic wave-vector direction